Study on the analytical model for load distribution of multiple-ring-stiffened tube-gusset joints considering ring stiffness. (May 2023) - Sitong, Wei; Jinghua, Zhang; Chao, Zhao; Xueming, Wang; Qing, Sun
Abstract: Tube-gusset joints in transmission towers are usually reinforced by multiple ring stiffeners. The external loads exerted on the joints will ultimately be borne by the rings. Therefore, it is crucial to understand how the loads are distributed among the ring stiffeners during the design stage. To this end, a solution was introduced in the pertinent Japanese standard. However, this solution has been derived based on the assumption of rigid ring stiffeners. Namely, the load distribution is irrelevant to the features of each ring stiffener, e.g., height, thickness, and spacing. This has led to inaccurate results in the solution. As an advancement from it, an improved analytical model is proposed in this paper. The tube-gusset joints with multiple ring stiffeners (MS-Joints) are described by the spring-mounted rigid beam model, in which the ring stiffeners are represented by spring supports. An analytical solution is therefore derived by incorporating flexible ring stiffeners. The validity of the solution is examined by the test-validated finite element method. Comparisons with the numerical results prove that the proposed solution is significantly more accurate than the conventional one. It is then used to conduct parametric analyses on the features of the ring stiffeners. The results reveal that the load distribution is most sensitive to the height of the ring stiffeners. Also, ring stiffeners should be arranged symmetrically to the middle line of the gusset plate to exploit their bearing capacities.